2002
DOI: 10.1021/np0106337
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Quinone Reductase by Withanolides

Abstract: Thirty-seven naturally occurring withanolides (1-37), previously isolated in our laboratories, were evaluated for their potential to induce quinone reductase with cultured murine hepatoma cells (Hepa 1c1c7). Spiranoid (29, 32) and 18-functionalized withanolides (2-5, 7-9, 24) were found to be potent inducers of the enzyme, while 5alpha-substituted derivatives exhibited weak activity. Preliminary studies were performed with compound 29 to evaluate enzyme-inducing capacity in multiple organ sites of BALB/c mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 19 publications
3
64
0
3
Order By: Relevance
“…One such compound, the spiranoid, jaborosalactone P (389), was selected to test its capacity to induce steady-state levels of quinone reductase in multiple organ sites of BALB/c mice. With jaborosalactone P-treated mice, a significant induction was observed in liver and colon, but not in lung, stomach, or mammary gland (253). This in vivo study confirmed the in vitro results, indicating that withanolides may function as potent phase II enzyme inducers.…”
Section: Cancer Chemopreventive Activitysupporting
confidence: 83%
See 1 more Smart Citation
“…One such compound, the spiranoid, jaborosalactone P (389), was selected to test its capacity to induce steady-state levels of quinone reductase in multiple organ sites of BALB/c mice. With jaborosalactone P-treated mice, a significant induction was observed in liver and colon, but not in lung, stomach, or mammary gland (253). This in vivo study confirmed the in vitro results, indicating that withanolides may function as potent phase II enzyme inducers.…”
Section: Cancer Chemopreventive Activitysupporting
confidence: 83%
“…In a broader study comprising withanolides from 13 Solanaceae species, 37 withanolides representative of a variety of structural types were evaluated for their potential to induce quinone reductase (253). Jaborosalactone 1 (397), jaborosalactone O (353), jaborosalactone P (389), trechonolide A (368), and withaphysalin J (320), were significant QR inducers with CD values in the range of 0.27-1.52 mM.…”
Section: Cancer Chemopreventive Activitymentioning
confidence: 99%
“…A pharmacologic study conducted on this plant indicated that a component withanolide, withaferin A, inhibits angiogenesis (4). Withanolides have also been reported to inhibit metastasis (5) and quinone reductase activity (6). Some of them have been shown to preferentially affect events in the cholinergic signal transduction cascade of the cortical and basal forebrain, indicating their promise for the treatment of Alzheimer's disease (7).…”
Section: Introductionmentioning
confidence: 99%
“…Estes foram primeiramente citados na literatura em 1962, mas sua elucidação estrutural sĂł aconteceu em 1966 com a descrição estereoquĂ­mica da vitaferina 1 (Figura 1) isolada das folhas de Withania somnifera, popularmente conhecida na Índia como Ashwaganha. 2 Os vitanolidos tĂȘm sido isolados de plantas de vĂĄrios gĂȘneros, como exemplo podem ser citados: Acnistus, [3][4][5][6][7][8] Datura, 9 Jaborosa, 10 Physalis 11 e Withania, 12,13 todos da famĂ­lia Solanaceae, e despertam interesse por apresentarem diversas atividades biolĂłgicas, algumas delas como antitumoral, 4-8 diurĂ©tica, 13 indução de quinona redutase 5,14 e imunossupressora. 15 Outros esteroides que sĂŁo encontrados na famĂ­la Solanaceae incluem glicosĂ­deos e alcaloides esteroidais, compostos presentes nos gĂȘneros Cestrum e Solanum, sendo este Ășltimo gĂȘnero o que possui o maior nĂșmero de espĂ©cies catalogadas.…”
Section: Introductionunclassified